2018
DOI: 10.15226/2475-4676/3/3/00144
|View full text |Cite
|
Sign up to set email alerts
|

Gout – Practicable Interdisciplinary Insights for the Clinician on a Surgeon’s Perspective

Abstract: Gout is a common systemic metabolic disease caused either by increased uric acid production or by decreased uric acid excretion potentially leading to crystal deposition of monosodium urate in various tissues and resulting in acute gouty attacks mainly initially presenting as mono arthritis of joints. The further course can be accompanied with development of chronic tophaceous gout with or without complications such as skin perforation of tophi accompanied with occurrence of chronic fistula and overlying bacte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…These results were consistent with the associations between PRKCZ and STK11 hypomethylation and development of gout ( Table 2 ). Family history of gout is associated with other markers of severity such as polyarticular gout and tophi formation [ 50 , 51 ]. These observations suggest that PRKCZ and STK11 hypomethylation could be associated with more severe gout phenotypes in addition to gout susceptibility.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These results were consistent with the associations between PRKCZ and STK11 hypomethylation and development of gout ( Table 2 ). Family history of gout is associated with other markers of severity such as polyarticular gout and tophi formation [ 50 , 51 ]. These observations suggest that PRKCZ and STK11 hypomethylation could be associated with more severe gout phenotypes in addition to gout susceptibility.…”
Section: Resultsmentioning
confidence: 99%
“…The results indicated that hypomethylation in PRKCZ and STK11 was associated with familial clustering of gout ( Supplementary Figure 71 ). Familial clustering of gout is associated with polyarticular manifestation and presence of tophi [ 50 , 51 ], both of which are indicative of severe gout. These findings suggest that PRKCZ and STK11 hypomethylation might impact not only disease susceptibility but might also impact family histories and clinical phenotypes in gout patients.…”
Section: Discussionmentioning
confidence: 99%